Concordance of temperature measurements on preterm and term infants using oesophageal (core), axilla & skin methods in a neonatal intensive care unit. Issue 6 (December 2022) - Smith, Jacqueline; Alcock, Gary; Monk, Barbara; Jones, Rhondda
Abstract: Aim: the aim of this contemporary paper is to investigate agreement between the axilla, core (oesophageal) and skin method of temperature taking. Design: A comparative descriptive design with a non-probability convenience sample used to describe the difference in recorded temperature by each method in preterm and term infants, gestational age from 24 weeks to term +14 days. Method: All infants born at 24 weeks and term plus 14 days gestation, admitted to NICU and received parental consent were enrolled in the study. Infants were nursed in various thermal environments. Oesophageal temperature was recorded using the InnerSense sensor/feeding tube (Philips Healthcare, axilla by the BD digital thermometer and skin temperature by the Philips skin temperature probe. Conclusion: The results of this study demonstrate that oesophageal and axilla temperature estimates are very similar, with most differences less than 0.5 °C (CC = 0.63). By contrast, a comparison of oesophageal and skin method temperature estimates shows a much weaker agreement (CC = 0.37). This study confirms that oesophageal temperature taken via the Philips InnerSense can be used safely, as it agrees with the axilla method. Infants nursed in the neonatal intensive care environment, especially when preterm or term with PPHN for example, have special requirements for temperature regulation and minimal handling.